Heat management solutions for the space camera: From design to orbital operations - Richa Hu; Min Zhang; Chunlong Liu; Qingwen Wu; Liang Guo (Case Studies in Thermal Engineering)
The camera mounted at the end of the space robot arm provides real-time visual monitoring and positioning functions during space missions. Its thermal design is crucial for ensuring both functionality and performance, particularly in challenging environments characterized by high radiation, extremely low temperatures, and vacuum conditions. Effective thermal management guarantees stable camera operation despite temperature fluctuations, ensuring both image quality and functional reliability. The integrated thermal design incorporates both passive and active controls, including cooling surfaces, multilayer insulation components, light shields, and heating loops. Simulation and experimental results show that, under low-temperature conditions, the active temperature control system effectively maintains the camera housing temperature above −50 °C, validating the stability of the thermal design. In high-temperature conditions, the camera housing temperature rises by 30 °C, reaching approximately 0 °C, confirming its efficient heat dissipation capability. Furthermore, after approximately 100 orbital cycles, the camera consistently stabilizes within the designed temperature range, affirming the precision and reliability of the thermal design. These findings offer essential insights for optimizing thermal management strategies in space cameras intended for complex space missions.